THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE IN NONPROFIT ORGANIZATION AT UNIT TRANSFUSI DARAH - Maradesa, Cicilia C.; Massie, James D. D. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Good corporate governance (GCG) can be implemented in nonprofit organization, especially implemented at UTD PMI in North Sulawesi. In North Sulawesi still has difficulty in blood stock. The blood target is 1.200 bags of blood per month but so far only 1.800 bags that can be fulfilled. Blood donor service is one of the activities/programs of PMI and it related to responsibility and fairness. Responsibility and fairness are the principles of GCG. To maintain good relations and build good trust of society, PMI needs to be implemented the GCG with the principles itself (TARIF). The research aimed to know the implementation of GCG in nonprofit organization PMI at UTD in North Sulawesi. This research is a qualitative research using case study analysis method that gathering primary data from in-depth interview of 12 respondents as the employees of PMI at UTD. The results of this research show that PMI at UTD in North Sulawesi has implemented GCG with its principles but still have the problem regarding the blood stock. The researcher recommend that the blood needs must be fulfilled, PMI at UTD in North Sulawesi should do more socializing, build good communication, invite the society to donate their blood.Keywords: good corporate governance, transparency, accountability, responsibility, independency, fairness.